2012
DOI: 10.21859/isv.6.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Fowl Adenovirus Associated with Inclusion Body Hepatitis in Iran

Abstract: Background and Aims: Inclusion body hepatitis (IBH) is one of the most important reemerging diseases in many countries with intensive poultry industries. In Iran, the etiological agent of IBH (fowl adenovirus) has not been yet confirmed. The aim of this study was the molecular detection and identification of fowl adenovirus involving IBH in chicken flocks in Iran. Materials and Methods: Polymerase chain reaction (PCR) and sequence analysis of L1 hexon gene was utilized to detect and to determinate the genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The main pathological findings of the present study are coincident with those previously described (Sandhu et al, 1994;Pilkington et al, 1997;Gaba et al, 2010;Hosseini & Morshed, 2012;Rahimi & Siavosh Haghighi, 2015). In this study, histopathological lesions of the liver did not reveal eosinophilic intranuclear inclusion bodies described by some authors (Sileo et al, 1983;Coussement et al, 1984;Riddell, 1984;Pass, 1987;Goryo et al, 1988;Schelling et al, 1989;Rahimi & Siavosh Haghighi, 2015) in cases of adenovirus IBH.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…The main pathological findings of the present study are coincident with those previously described (Sandhu et al, 1994;Pilkington et al, 1997;Gaba et al, 2010;Hosseini & Morshed, 2012;Rahimi & Siavosh Haghighi, 2015). In this study, histopathological lesions of the liver did not reveal eosinophilic intranuclear inclusion bodies described by some authors (Sileo et al, 1983;Coussement et al, 1984;Riddell, 1984;Pass, 1987;Goryo et al, 1988;Schelling et al, 1989;Rahimi & Siavosh Haghighi, 2015) in cases of adenovirus IBH.…”
supporting
confidence: 93%
“…Some studies in Canada supported the hypothesis that IBH in broilers is a primary disease without known immunosuppressive agents (Gomis et al, 2006). Also, previous studies in Iran did not mention any cooccurring disease or other predisposing factor in studied flocks (Hosseini & Morshed, 2012;Rahimi & Siavosh Haghighi, 2015). Hosseini & Morshed (2012) identified serotype 11 fowl adenovirus as the causative agent of IBH.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Hossini and Morshed identified FAdVs-11 serotype from dead 3-week-old broiler chicken flock and showed that this serotype caused clinical disease and mortality in this flock. 11 Since the primers used in this study can amplify DNA from all the 12 FAdV serotypes, it is unlikely that the negative results in some samples were due to PCR performance. Another possibility is that the viral load in the samples was below the detection limit.…”
Section: Discussionmentioning
confidence: 93%
“…FAdV-6 and FAdV-2 were detected from Saudi poultry flocks by Mohamed et al (15). In Lebanon, FAdV-11 was found in commercial broiler flocks (32), and in Iran, two FAdV species D and E (FAdV-11, FAdV-8b) were linked with outbreaks of IBH (7,16,18). Similarly, an investigation of the outbreaks of IBH in Australia, South Africa, Austria, and Spain reported FAdV-8b or FAdV-11 in broiler flocks (10,24,30,34).…”
Section: Discussionmentioning
confidence: 99%